Prevalence, antibiotic susceptibility and pathogenicity of rhodococcus equi in horse faeces and soils from selected stud farms in Peninsular Malaysia - Shari, Mohammad Fhitri (2014)
Rhodococcus equi is considered as a major bacterial veterinary pathogen that is difficult to treat amongst the important diseases in the equine industry. It has been isolated from clinical specimens from human, various species of animals as well as environmental samples such as soil, air, bedding materials and others in many countries but reports are scarce in South East Asian countries including Malaysia. This study was conducted to determine the appropriate selective medium for the isolation of R. equi, to determine its prevalence in horse’s faeces and soil in selected farms, to determine the antimicrobial susceptibility patterns and to evaluate the pathogenicity of the virulent R. equi isolates. Two types of selective medium; Nalidixic Acid-Novobiocin-Actidione-Tellurite medium (NANAT) and modified Ceftazidime-Novobiocin medium (m-CAZ) were evaluated to isolate R. equi from clinical and environmental samples. Samples were cultured on both medium and presumptive isolates were identified using conventional biochemical test and confirmed using species specific polymerase chain reaction (PCR). The m-CAZ medium was shown to be the better selective medium with 36/81 (44.44%) successful isolations compared to none (0%) on the NANAT. Prevalence of R. equi in selected farms were conducted in four farms (A, B, C and D) comprising of 103 healthy animal faeces (mares, n=59; foals, n=44) and 139 soil samples. The prevalence of R. equi from farms A, B, C and D was recorded as 14.29% (6/42), 38.60% (22/57), 52.81% (47/89) and 42.59% (23/54) respectively. Of 98 R. equi isolates collected, 53.06% (52/98) were isolated from soil while the remaining was derived from faeces. From these number, 3.85% (2/52) of soil isolates and 6.52% (3/46) of faecal isolates were virulent detected through multiplex PCR. All five virulent isolates were from farm C. The isolates were subjected to antibiotic sensitivity test using disc diffusion technique. All were tested against 12 different antibiotics namely Ampicillin, Azithromycin, Ceftiofur, Cephalexin, Doxycycline, Enrofloxacin, Erythromycin, Gentamicin, Levofloxacin, Oxytetracycline, Penicillin and Streptomycin. Six of 98 isolates (6.12%) were susceptible to all antibiotics, 92 of 98 isolates (93.88%) were resistant to at least one antibiotic, 47.96% (47/98) showing mono-resistant and 45.92% (45/98) were multidrug resistant. The isolates showed the highest susceptibility rate against four antibiotics which were Doxycycline, Levofloxacin, Enrofloxacin and Gentamicin. Besides that, 93.88% (92/98) isolates were intermediately resistant to Streptomycin and 2.04% (2/98) were found to resistant to Erythromycin although others not. Six isolates (virulent, n=5; avirulent, n=1) were subjected to pathogenicity test in mice. The results revealed that three of virulent isolates caused death in mice while others did not after being inoculated intraperitoneally. The avirulent isolate and the other two virulent isolates did not cause death in tested mice. Postmortem on the dead mice showed that the major visceral organ affected were lung, liver and spleen while others showed non significant lesion. All affected lung were haemorrhagic while all affected liver and spleen were congested. Histological examination proved that all of these visceral organs were severely damaged with the lesion score of three instead of one or two. In conclusion, this study showed low prevalence of virulent R. equi in all selected stud farms in Peninsular Malaysia.